Effect of toe box size on basketball-specific movement performance - Zhang, Jialu; Chu, Zhaowei; Bai, Taoping; Zhang, Ming; Ren, Weiyan; Li, Zhongyou; Jiang, Wentao (Frontiers in Bioengineering and Biotechnology, 2025)
PurposeWhile an expanded toe box (TB) design offers notable benefits for foot health in basketball players, its impact on movement performance remains insufficiently elucidated. This study aimed to explore this relationship and inform the development of advanced shoe designs.MethodsWe conducted a controlled laboratory study with a within-subject crossover design. Thirty basketball players (25 males, five females; aged 18–20 years) performed standardized 5-m sprints, 180° lateral shuffling, and 45° sidestep cutting in six shoe versions. These versions systematically altered the toe allowance dividing line (TADL) (0, 1.5, 3 mm) and the sole center line (SCL) rotation (0°, 2°). Movement time, ground reaction forces, propulsion impulse, and joint kinematics were measured using optical timing systems, force platforms, and motion capture.ResultsA 3-mm TADL extension significantly improved performance, reducing sprint, lateral shuffling, and sidestep cutting times by 6.53% (P < 0.01), 3.49% (P < 0.01), and 7.69% (P < 0.01), respectively, and increased propulsion impulse by 27.27% (P < 0.01). A 1.5-mm TADL extension improved sprint time by 4.02% (P < 0.05), though the effects on other movements were limited. A 2° SCL rotation showed no significant performance improvements (P > 0.05).ConclusionOur findings suggest that shoes with enlarged TB improve both forward and lateral movements. Inward TADL extension optimizes performance by enhancing foot mobility and force transmission, while SCL rotation offers minimal benefits. These findings challenge the conventional tight-fitting shoe designs and provide insights for designing footwear that enhances agility and reduces injury risks.